ANALISIS MANAJEMEN SARANA DAN PRASARANA DI SMK NEGERI 4 KOTA PONTIANAK - Feryna, Feryna; Ulfah, Maria; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze and describe the management of facilities and infrastructure carried out by SMK Negeri 4 Kota Pontianak. This study uses a qualitative approach. Data sources were obtained from facilities and infrastructure as well as 14 K3. Data were collected using interviews and triangulation techniques. The results of the study show that (1) Planning of facilities and infrastructure shows that the planning carried out is not appropriate because of the absence of procedures established by the school, (2) Procurement of facilities and infrastructure shows the school has procedures for submission of equipment and procurement of goods but has not been properly realized, (3) Inventory of facilities and infrastructure is carried out manually and incompletely, (4) Storage and maintenance of facilities and infrastructure are not carried out properly because there is no planning prepared for maintenance, limited procurement of goods, and incomplete inventory, (5 ) The elimination of facilities and infrastructure is not carried out due to cost problems resulting in irregular spatial planning due to the accumulation of damaged goods in each skill competency, (6) Supervision is not carried out properly due to improper planning, difficult procurement, inventor information that does not meet guidelines, maintenance or limited storage, and deletions that are not carried out. Keywords: School Facilities, Infrastructure Management